2007
DOI: 10.1002/lt.21095
|View full text |Cite
|
Sign up to set email alerts
|

Expanded criteria for liver transplantation in patients with hepatocellular carcinoma: A report from the International Registry of Hepatic Tumors in Liver Transplantation

Abstract: TXHepatocellular carcinoma (HCC) is a common indication for liver transplantation (LT). Currently, deceased donor LT is approved by the United Network for Organ Sharing for patients with HCC who meet the Milan criteria of a single tumor up to 5 cm or up to 3 tumors up to 3 cm as determined by imaging studies. We analyzed data in the International Registry of Hepatic Tumors in Liver Transplantation from 1,206 patients with HCC. Tumor size and number were determined by gross pathologic examination. Kaplan-Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(135 citation statements)
references
References 44 publications
4
128
0
3
Order By: Relevance
“…Our study results were consistent with previous studies that showed no survival differences in patients with HCC for both those that met and those exceeded the Milan criteria [9,16,18] and for those that met both the Milan and UCSF criteria [17,19]. Although the UCSF criteria have been shown to be associated with a longterm survival similar to the Milan criteria [23][24][25], little is known with regard to the outcomes of patients with HCC that exceed the UCSF criteria. In one of the largest series, Duff et al reported a 3-year survival of 83 % for those that met the UCSF criteria and 48 % for those exceeded the UCSF criteria [20].…”
Section: Discussionsupporting
confidence: 91%
“…Our study results were consistent with previous studies that showed no survival differences in patients with HCC for both those that met and those exceeded the Milan criteria [9,16,18] and for those that met both the Milan and UCSF criteria [17,19]. Although the UCSF criteria have been shown to be associated with a longterm survival similar to the Milan criteria [23][24][25], little is known with regard to the outcomes of patients with HCC that exceed the UCSF criteria. In one of the largest series, Duff et al reported a 3-year survival of 83 % for those that met the UCSF criteria and 48 % for those exceeded the UCSF criteria [20].…”
Section: Discussionsupporting
confidence: 91%
“…4,12,13,16,19 In that sense, the use of radiologic tests (triphasic computed tomography, magnetic nuclear resonance, or contrast ultrasound) on the day of OLT might be an option to solve that problem. On the other hand, when variables that could be assessed in the pre-OLT period were analyzed, bilobar involvement and a poor differentiation degree proved to be 2 independent factors associated with radiologic underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Because of these limitations, several recent studies have evaluated whether more liberal criteria for tumor staging could be adopted without significant impairment of patient survival or tumor recurrence. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Presently, however, there is no consensus yet on recommending the expanded criteria as the standard of care. 20,21 In view of these uncertainties, we have considered OLT for patients with cirrhosis with up to 3 tumors, with none larger than 5 cm, and a cumulative tumor burden Յ 10 cm without evidence of macrovascular invasion, extrahepatic spread, or nodal involvement.…”
mentioning
confidence: 99%
“…However, the criteria proposed by the University of Pittsburgh and some groups in Europe are based, at least in part, on pathological features (nodal invasion, grade, vascular invasion) that are not usually available before transplantation (9,21,50,68) . By contrast, the MC, UCSF and Onaca et al (42) proposal rely on factors (tu- ITT = intention to treat ¥ = patient survival (PS) ² = recurrence free rate (RR) Staging refers to the method used for tumor staging. P = pretransplant radiology; R = explant tumor pathology; NA = not available mor size and number) that can be determined by preoperative imaging, however, such criteria must consider the limitations of imaging studies (7,23,48,55,56,59,60) .…”
Section: Discussionmentioning
confidence: 99%